CoDiLe: An instrument for evaluating the Spanish-language disciplinary knowledge of pre-service teachers - María Teresa Muedra Pedris; Ángela Gómez López; Eva Morón Olivares; Manuel Monfort Pañego (Revista Española de Pedagogía)
In recent decades, various research works have focussed on assessing teachers’ pedagogic knowledge, especially in science and mathematics. However, few works in the field of language have designed and validated tools for this purpose. The present work aims to progress in this line of research by designing and validating a questionnaire to assess the Spanish-language disciplinary knowledge of pre-service teachers. Spanish students from the degree in Primary School Education and Master’s in Secondary Education as well as experts in didactics of language and in validating questionnaires participated. To analyse its content validity, we used the Delphi method and, to study consistency, we performed a psychometric analysis using the test–retest reliability method. The instrument was found to be consistent and valid. The results were below what was expected and revealed that the sample showed a clear shortcoming in disciplinary content in Spanish language. These data seem to be in line with those obtained in other areas. Consequently, CoDiLe can contribute to defining and remedying these possible deficiencies by providing consistent data to teacher trainers to guide their practice more effectively.